EDUKASI RASIONALITAS PENGGUNAAN ANTIBIOTIK UNTUK MENCEGAH RESISTENSI DI SMK AL RAZI SINAR HARAPAN - Sembiring, Pintata (INSTITUT KESEHATAN DELI HUSADA, 2025)
Antibiotic resistance has become one of the most serious global health threats due to the irrational use of antibiotics, such as self-medication and non-adherence to medical advice. A lack of public understanding regarding the correct use of antibiotics is a primary driver of this problem. This Community Service (PKM) activity, proposed by students of the Apothecary Profession Program at the Deli Husada Deli Tua Health Institute, aims to increase awareness and compliance regarding the proper use of antibiotics to prevent resistance. The activity will be conducted as a health education program targeting tenth-grade students at SMK Al Razi Sinar Harapan in Medan. The method used is interactive counseling and socialization to deliver information about the dangers of resistance, the correct way to use antibiotics, and the negative impacts of their misuse. Through this educational initiative, students are expected to become agents of change in their communities, promoting the wise and responsible use of antibiotics.